MICROBIOME-ORIENTED APPROACH IN THE TREATMENT OF BRONCHOPULMONARY PATHOLOGY IN CHILDREN: CLINICAL EFFECTIVENESS AND PROSPECTS FOR PERSONALIZATION - Mamadzhanova N. A.; Ashurova D. T. (Modern American Journals, 2025)
Recurrent and chronic diseases of the bronchopulmonary system in children occupy one of the leading positions in the structure of childhood morbidity. Modern scientific data confirm the key role of the microbiota of the respiratory tract and the intestine in modulating the immune response, inflammatory processes and restoration of the mucous membranes. This is especially relevant for young children, when the immune system is in a stage of active formation. Dysbiosis of the oropharynx and intestine may contribute to a prolonged course of respiratory diseases, frequent exacerbations and a decrease in the effectiveness of standard therapy.